Analisis Penggunaan Artificial Intelligence Terhadap Efisiensi Produksi Jasa Kreatif Freelancer Kabupaten Bone Dalam Perspektif Ekonomi Syariah - Titiek Muthmainnah; Muhsyi Alyah; Asni Gusmiarni; Sitti Nikmah Marzuki; Arifin Sahaka (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2026)
This study aims to analyze the utilization of AI in the production activities of creative service freelancers in Bone Regency, examine the efficiency gained through its implementation, and explore its use from the perspective of Islamic economics. This research employed a qualitative method with a descriptive approach. Data were collected through observation, semi-structured interviews, and documentation involving four freelancers working in website and application development, graphic design, photography, and videography. The findings reveal that AI has been integrated into various stages of production, including idea generation, technical problem-solving, asset creation, and editing processes. The use of AI contributes to faster task completion, easier access to references, and more efficient production workflows without eliminating the role of humans as the primary decision-makers. Furthermore, freelancers adapt to technological advancements by emphasizing creativity, experience, and service quality to maintain their competitiveness. From the perspective of Islamic economics, the use of AI is considered permissible as long as it adheres to the principles of honesty (shidq), justice ('adl), and non-maleficence (la dharar). Therefore, the efficiency generated by AI remains aligned with ethical values and social responsibility in production activities.